2016
DOI: 10.11604/pamj.2016.24.258.7567
|View full text |Cite
|
Sign up to set email alerts
|

Understanding abortion-related stigma and incidence of unsafe abortion: experiences from community members in Machakos and Trans Nzoia counties Kenya

Abstract: IntroductionThe rate of unsafe abortions in Kenya has increased from 32 per 1000 women of reproductive age in 2002 to 48 per 1000 women in 2012. This is one of the highest in Sub-Saharan Africa. In 2010, Kenya changed its Constitution to include a more enabling provision regarding the provision of abortion services. Abortion-related stigma has been identified as a key driver in silencing women's ability to reproductive choice leading to seeking to unsafe abortion. We sought to explore abortion-related stigma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 9 publications
0
36
2
Order By: Relevance
“…For example, one woman shared: "I was afraid of whether someone would scold me [ (India, age 28). Similarly, another woman said she felt "shy to come back to that place [the clinic]" if she became pregnant after they provided her with contraceptives (India, focus group participant, aged [24][25][26][27][28].…”
Section: Women's Attitudes Towards Abortion Generally and Their Own Amentioning
confidence: 99%
See 3 more Smart Citations
“…For example, one woman shared: "I was afraid of whether someone would scold me [ (India, age 28). Similarly, another woman said she felt "shy to come back to that place [the clinic]" if she became pregnant after they provided her with contraceptives (India, focus group participant, aged [24][25][26][27][28].…”
Section: Women's Attitudes Towards Abortion Generally and Their Own Amentioning
confidence: 99%
“…4,17 In 2013, the Kenyan Ministry of Medical Services withdrew the previously published national "Standards and Guidelines for Reducing Morbidity and Mortality from Unsafe Abortion in Kenya" without explanation and warned health providers against participating in abortion training. 23,24 These actions, possibly in response to pressure from anti-abortion groups, resulted in confusion among service providers and people seeking care with regards to the legality of abortion service provision. 23 The withdrawal of the guidelines and the confusion about the law have been found to contribute to abortion stigma, which can hinder access to care and result in women seeking unsafe abortion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This compound stigma is a powerful inhibiting force leading to severe consequences for women, including death, further abuse of victims, and poor quality of care 19 . Similarly, a study from Kenya also highlighted abortion related stigma as a key driver in silencing women's ability to seek help, and suggested that in communities where abortion stigma is higher, women are more likely to resort to unsafe abortion, even when legal options are available 20 . While this evaluation was not designed as a before/after study, and monitoring data was collected in the midst of ongoing initiatives to address unsafe abortions, it is important to highlight some of the differences observed between the two data collection periods to demonstrate the trajectory in the two and a half years.…”
Section: Discussionmentioning
confidence: 99%